PENGARUH PENAMBAHAN LAKTOSA DI DALAM PENGENCER TRIS DAN SITRAT TERHADAP KUALITAS SEMEN CAIR SAPI ANGUS (The effect of additional lactose in tris and citrate diluents on the quality of liquid semen of angus cattle) - Satria J.S. Rihileo; Kirenius Uly; Wilmientje M. Nalley; Hendriana L.L. Belli (JURNAL NUKLEUS PETERNAKAN, 2023)
Lactose is the only carbohydrate found in milk and serves as an additional source of energy and protects the plasma membrane of spermatozoa from damage due to cold shock during storage at low temperatures. The purpose of this study was to examine the effect of adding lactose in tris and citrate diluents on the quality of liquid semen. One 3 year old angus cow in healthy condition. Semen was diluted with diluent P0: Tris-egg yolk (T-EY) 100%, P1: Citrate-egg yolk (C-EY) 100%, P2: T-EY 50 %+C-EY 50%, P3: T-EY 50%+ C-EY 50%+Lactose 1.5g, P4: T-EY 50%+ C-EY 50%+Lactose 3.0g, P5: T- EY 50%+ C-EY 50%+Lactose 4.5g. After diluted cement is stored at a temperature of 3-5oC. Semen was evaluated post dilution and every 24 hours of storage for motility, viability, abnormalities and survival of spermatozoa. The data were analyzed using analysis of variance (ANOVA) and Duncan's test. The results of this study showed that the P3 (P>0.05) treatment was the best compared to other treatments, namely the percentage of spermatozoa motility values of 43.50±2.23%, spermatozoa viability was 53.07±3.36%, spermatozoa abnormalities were 8.01±2.14%, and spermatozoa survival was 6.60.00±0.54 days. The results of this study indicate that using a combination of T-EY and C-EY diluents with the addition of 1.5g lactose is the best diluent in maintaining the quality of liquid semen of angus cattle.